Investigation of the relationships between sports anxiety, positive thinking skills, and life satisfaction in male athletes - Tolukan, Ersan; Yildiz, Aydiner Birsin; Yenel, Ibrahim Fatih; Yalcin, Ilimdar; Stoica, Leonard; Iordan, Daniel-Andrei; Ilie, Onu (Frontiers in Psychology, 2024)
Sports anxiety is an important obstacle for athletes’ performance, negatively affecting their life satisfaction levels. Positive thinking skills can contribute to overcoming such negative conditions. This study explored the relationships between sport anxiety, positive thinking skills, and life satisfaction in male athletes. A total of 338 male athletes participated voluntarily, using convenience sampling. The study employed a relational survey model, and data were collected through the Sports Anxiety Scale-2, Positive Thinking Skills Scale, and Life Satisfaction Scale. Analyses, including Pearson’s correlation, were performed using the JAMOVI program, with mediation analysis verified through bootstrapping. Results indicated a negative correlation between sport anxiety and life satisfaction, and a positive correlation between positive thinking skills and life satisfaction. Moreover, positive thinking skills were found to moderate the relationship between sport anxiety and life satisfaction. These insights underscore the value of developing positive thinking skills to help athletes reduce anxiety and enhance their life satisfaction. Therefore, incorporating strategies to foster these skills in training programs could be crucial for improving athletes’ overall wellbeing.